16th International Symposium on Advanced Vehicle Control c - Mastinu, Giampiero; Braghin, Francesco; Cheli, Federico; Corno, Matteo; Savaresi, Sergio M.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access book highlights the latest advances, innovations, and applications in the field of vehicle systems dynamics and control, as presented by leading international researchers at the 16th JSAE International Symposium on Advanced Vehicle Control (AVEC), held at Politecnico di Milano, Milan, Italy, on September 2-6, 2024. It covers a diverse range of topics such as vehicle dynamics theory, steering, brake, tire, suspension, chassis control, powertrain, electrified vehicles, stability enhancement systems, driver-vehicle systems, advanced driver assistance systems and automated driving systems, driving simulator dynamics and control. The contributions, which were selected by means of a rigorous international peer-review process, present a wealth of exciting ideas that will open novel research directions and foster multidisciplinary collaboration among different specialists.
Keywords: Vehicles; Automotive engineering; Transportation engineering; Traffic engineering; Control engineering; Robotics; Automation; Vehicle Engineering; Automotive Engineering; Transportation Technology and Traffic Engineering; Control, Robotics, Automation